DEVELOPING LEARNING MEDIA FOR WRITING ANALYTICAL EXPOSITION TEXT BY USING ADOBE FLASH PROFESSIONAL CS5 FOR THE ELEVENTH GRADE STUDENTS OF SMA SWASTA NURUL AMALIYAH TANJUNG MORAWA - Winka Wardhani; Indra Hartoyo; Immanuel Prasetya Gintings (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
The aim of this study was to develop learning media for writing analytical exposition text by using Adobe Flash Professional CS5 for the eleventh students of SMA Swasta Nurul Amaliyah Tanjung Morawa. This study was conducted by using Research and Development (R & D) design through six stages; gathering data and information, analyzing data, designing media, validating by the experts, revising and final products. The subject of the study was grade XI of SMA Swasta Nurul Amaliyah Tanjung Morawa. The data were gathered by administering interview to English teacher and distributing questionnaire to 30 respondents to get the students’ needs. The interview and questionnaire result proved that the students need a learning media in teaching writing which can help the students to understand about the analytical exposition text. The learning media of Adobe Flash Prrofessional CS5 was validated by experts. The average score is 4.62. It means the developed learning media by using Adobe Flash Professional CS5 is relevant or appropriate and categorized as a very good learning media for students at SMA Swasta Nurul Amaliyah Tanjung Morawa.  Keywords: Research and Development (R&D), Adobe Flash Professional CS5, Analytical Exposition Text